1983
DOI: 10.1007/bf00165610
|View full text |Cite
|
Sign up to set email alerts
|

Syncope from head and neck cancer

Abstract: We have examined 17 patients suffering from recurrent syncope caused by carcinoma of the head and neck. The tumor originated in the mouth in seven, larynx in six, nasopharynx in three and parotid gland in one, and involved cervical lymph nodes at diagnosis in 12. Sixteen patients had previously had radical neck dissections and 12 had had radiation therapy. Recurrent carcinoma was present in 16. Spells resolved spontaneously in four, improved with treatment in 11 and continued in two. The syncope was spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 54 publications
0
44
1
1
Order By: Relevance
“…Induction chemotherapy was chosen over Surgery or radiotherapy because Surgery is often palliative only and radiotherapy poses the risk of a syncopal event in an unmonitored environment. 15,16 Our patient did not have any further episodes of syncope.…”
Section: Discussionmentioning
confidence: 55%
“…Induction chemotherapy was chosen over Surgery or radiotherapy because Surgery is often palliative only and radiotherapy poses the risk of a syncopal event in an unmonitored environment. 15,16 Our patient did not have any further episodes of syncope.…”
Section: Discussionmentioning
confidence: 55%
“…Conditions in this group comprise neurocardiogenic (vasovagal) syncope, situational syncope, carotid sinus syndrome and glossopharyngian neuralgia [3]. Malignancy-related reflex syncope is rare: in a series of 4,500 patients with cancer of the head and neck, the prevalence of syncope was estimated at 0.4% [4]. Patients with advanced tumoral disease at diagnosis and those with a history of neck surgery appear to be at greater risk of developing syncope [4].…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy-related reflex syncope is rare: in a series of 4,500 patients with cancer of the head and neck, the prevalence of syncope was estimated at 0.4% [4]. Patients with advanced tumoral disease at diagnosis and those with a history of neck surgery appear to be at greater risk of developing syncope [4]. Syncope may be an early sign of neck or cervical cancer [5] and even the sole sign of recurrent disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…Macdonald et al 2 reported 17 patients with recurrent syncopc from more than 4500 patients with head and neck cancer seen over a 12-year period, an incidence of less than 0.4%; however, half the patients were seen during the last 2 years, suggesting underrecognition of the problem. The tumor arose in the mouth in 7, the larynx in 6, nasopharynx in 3, and the parotid gland in 1 patient(s).…”
Section: Fig Imentioning
confidence: 99%
“…It is presumed, therefore, that invasion of the regional neurovascular bundle occurred, with involvement of the left vagus as well as regional sympathetic nerves. This resulted in intermittent afferent impulses causing efferent: (1) sympathetic inhibition with vasodepressor response5 and, (2) variable, but usually mild, parasympathetic cardioinhibitory effects.…”
Section: Fig Imentioning
confidence: 99%